Optimization of arc ignition process for machines of arc dimensional machining - Savelenko, Gregory; Yermolaev, Yury; Yuriev, Vitaly (Technology audit and production reserves, 2016)
The article examines the arc ignition at the arc dimensional machining (ADM). The audit found that: − This process not paying attention in scientific literature. − Feed rate of the electrode-tool with no arc combustion is set non-optimal. The main aim of research is to optimize the process of electrode-tool feed rate at the arc ignition and, thus, reduce shock loads to the electrode-tool. The nature of the change of the working fluid pressure in the electric erosion chamber at arc ignition is given. The pressure value is experimentally determined at which the automatic change of the maximum rate to working is ensured by the system of automatic feed of the electrode-tool to the workpiece. A functional of optimal arc ignition process of arc dimensional machining is proposed. It is possible to determine the maximum permissible rate of electrode-tool feed and reduce the likelihood of tool failure during the arc ignition. Thus, during machining due to rapid electrode-tool feed in the machining area, the technological operation time is decreased. Research results can be used by designers that create an automatic system of electrode-tool feed at dimensional (ADM), arc (EAM), blasting (BEAM) and other related electric erosion methods of metal machining.